2021
DOI: 10.1007/s40820-021-00747-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Microcapsules with Stem Cell Encapsulation for Bone Repair

Abstract: Bone defects caused by trauma, tumor, or osteoarthritis remain challenging due to the lack of effective treatments in clinic. Stem cell transplantation has emerged as an alternative approach for bone repair and attracted widespread attention owing to its excellent biological activities and therapy effect. The attempts to develop this therapeutic approach focus on the generation of effective cell delivery vehicles, since the shortcomings of direct injection of stem cells into target tissues. Here, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 50 publications
0
65
0
Order By: Relevance
“…Microencapsulation techniques are used increasingly in industries such as food, cosmetic, pharmaceutical, biomedical, and materials or textile. A few examples of recent biomedical-oriented microencapsulation research are given in refs . Certain fields of application require a precise control of the capsule properties (size monodispersity, shape regularity, controlled mechanical properties and porosity, aseptic production, high production rates), which is difficult to satisfy using standard encapsulation technologies such as spray drying or coating.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation techniques are used increasingly in industries such as food, cosmetic, pharmaceutical, biomedical, and materials or textile. A few examples of recent biomedical-oriented microencapsulation research are given in refs . Certain fields of application require a precise control of the capsule properties (size monodispersity, shape regularity, controlled mechanical properties and porosity, aseptic production, high production rates), which is difficult to satisfy using standard encapsulation technologies such as spray drying or coating.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al. used microfluidic electrospray technology to prepare biomass-carrying stem cell microcapsules for the treatment of bone defects and applied them in animal experiments [ 69 ]. Studies showed that the microcapsules prepared using this method had good compatibility and therapeutic effects, and had broad development prospects in the tissue engineering and medical fields.…”
Section: Processing Methods Of Microspheresmentioning
confidence: 99%
“…Hydrogel materials have good application value in ensuring the activity of growth factors and stem cells. 29,30 Therefore, as a kind of injectable hydrogel, the S1P@MSNs/ AHA/NOCC hydrogel could serve as a drug release system to improve the bioactivity of implants by a simple combination between the hydrogel and other implants (Fig. 7A).…”
Section: Subcutaneous Embeddingmentioning
confidence: 99%